Alzheimer's neuroinflammation: A crosstalk between immune checkpoint PD1-PDL1 and ApoE-Heparin interactions?. (July 2022) - Patil, Sachin P.; DiFlumeri, Juliette; Wellington, Justin; Fattakhova, Elena; Oravic, Michael
Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by amyloid beta (Aβ) plaques, neurofibrillary tangles (NFTs) and neuroinflammation that precedes Aβ and NFTs. Furthermore, Apolipoprotein E (ApoE), the most significant risk factor of late-onset AD, has been shown to play an isoform-specific role in AD pathogenesis, with ApoE4 conferring a significantly higher risk while ApoE2 being protective (ApoE4 > ApoE3 > ApoE2). Therefore, there is a significant interest in studying the underlying mechanisms involved in ApoE isoform specific effects. One such possible mechanism is the potential role of ApoE-Heparin interaction in AD-associated neuroinflammation. Heparin is an anticoagulant secreted by brain resident mast cells that are the "first-responders" to neuroinjury. Indeed, ApoE has been shown to exhibit isoform-specific binding with Heparin (ApoE4 > ApoE3 > ApoE2), which may explain the observed ApoE isoform-specific risk for AD. In support, the Christchurch mutation in ApoE3 (ApoE3ch), observed to be highly protective against AD, was shown to not bind to Heparin at all. Taken together, these data may emphasize a potential role of ApoE-Heparin binding in triggering neuroinflammation and downstream neurodegeneration in AD, in turn presenting a fundamentally novel therapeutic target against AD. Therefore, we hypothesize that targeting mast cells through direct activation of their co-inhibitory PD1-PDL1 pathway, may lead to decreased expression of Heparin by mast cells, which in turn may assist in mitigating the pathological ApoE-Heparin interaction and detrimental neuroinflammation. It is noteworthy that the checkpoint protein PD1 is shown to play a role in regulating growth and activation of human mastocytes, thus further supporting our hypothesis.